Accrual of Older Patients With Breast Cancer to Alliance Systemic Therapy Trials Over Time: Protocol A151527 - Freedman, Rachel A. (J Clin Oncol, 2017)
PURPOSE: Despite increasing awareness of accrual challenges, it is unknown if accrual of older patients to breast cancer treatment trials is improving. METHODS: We examined accrual of older patients to Alliance for Clinical Trials in Oncology systemic therapy breast cancer trials during 1985-2012 and compared disease characteristics and reasons for therapy cessation for older (age ≥ 65 years and ≥ 70 years) versus younger (age < 65 years and < 70 years) participants. To examine accrual trends, we modeled age as a function of time, using logistic regression. RESULTS: Overall, 17% of study participants were ≥ 65 years of age. Approximately 15%, 24%, and 24% of participants in adjuvant, neoadjuvant, and metastatic trials were age ≥ 65 years, and 7%, 15%, and 13% were age ≥ 70 years, respectively. The odds of a patient age ≥ 65 years enrolling significantly increased over time for adjuvant trials (odds ratio [OR] per year, 1.04; 95% CI, 1.04 to 1.05) but decreased significantly for neoadjuvant and metastatic trials (OR, 0.62; 95% CI, 0.58 to 0.67 and OR, 0.98, 95% CI, 0.97 to 1.00). Similar trends were seen for those age ≥ 70 years but these were statistically significant for adjuvant and neoadjuvant trials only (OR, 1.05, 95% CI, 1.04 to 1.07; and OR, 0.57, 95% CI, 0.52 to 0.62). In general, those age ≥ 65 years (v those < 65 years) in adjuvant studies had a higher mean number of lymph nodes involved and more hormone receptor-negative tumors, although tumor sizes were similar. Early protocol treatment cessation was also more frequent in those age ≥ 65 years (50%) versus < 65 years (35.9%) across trials. CONCLUSION: Older patients with breast cancer remain largely underrepresented in cooperative group therapeutic trials. We observed some improvement in accrual to adjuvant trials but worsening of accrual for neoadjuvant/metastatic trials. Novel strategies to increase accrual of older patients are critical to meaningfully change the evidence base for this growing patient population.